The Use of Artificial Intelligence in Distance Education - Krystian Tuczyński (Journal of Modern Science)
In this article, the examination of the influence of artificial intelligence (AI) on the educational process is conducted, with a particular focus on its impact on individualized teaching, the monitoring of educational progress, and student motivation. The discussion delves into diverse AI applications, including the customization of educational materials, adaptive progress tracking, and the introduction of innovative motivational techniques. Emphasis is placed on the positive aspects of incorporating AI into education, while concurrently underlining the importance of using this technology with awareness and discretion. Furthermore, the article seeks to dispel common misconceptions about the role of AI, particularly in generating educational content, and stresses the irreplaceable role of the teacher as a mentor in the learning process. A critical point is made about the imperative need to educate all participants involved in the educational sphere to effectively leverage the potential benefits of artificial intelligence.